TLR2, TLR4 AND MyD88 Mediate Allergic Airway Disease (AAD) and Streptococcus pneumoniae-Induced Suppression of AAD - Thorburn, Alison N. (PLoS One, 2016)
BACKGROUND: Exposure to non-pathogenic Streptococcus pneumoniae and vaccination are inversely associated with asthma. Studies in animal models demonstrate that airway administration of S. pneumoniae (live or killed), or its vaccines or components, suppresses the characteristic features of asthma in mouse models of allergic airway disease (AAD). These components could be developed into immunoregulatory therapies. S. pneumoniae components are recognized by Toll-like receptors (TLR) 2 and TLR4, and both induce inflammatory cell responses through the adaptor protein myeloid differentiation primary response gene 88 (MyD88). The involvement of TLR2, TLR4 and MyD88 in the pathogenesis of AAD and asthma is incompletely understood, and has not been studied in S. pneumoniae-mediated suppression of AAD. We investigated the role of TLR2, TLR4 and MyD88 in the development of AAD and S. pneumoniae-mediated suppression of AAD. METHODS AND FINDINGS: OVA-induced AAD and killed S. pneumoniae-mediated suppression of AAD were assessed in wild-type, TLR2(-/-), TLR4(-/-), TLR2/4(-/-) and MyD88(-/-) BALB/c mice. During OVA-induced AAD, TLR2, TLR4 and MyD88 were variously involved in promoting eosinophil accumulation in bronchoalveolar lavage fluid and blood, and T-helper type (Th)2 cytokine release from mediastinal lymph node T cells and splenocytes. However, all were required for the induction of airways hyperresponsiveness (AHR). In S. pneumoniae-mediated suppression of AAD, TLR2, TLR4 and MyD88 were variously involved in the suppression of eosinophilic and splenocyte Th2 responses but all were required for the reduction in AHR. CONCLUSIONS: These results highlight important but complex roles for TLR2, TLR4 and MyD88 in promoting the development of OVA-induced AAD, but conversely in the S. pneumoniae-mediated suppression of AAD, with consistent and major contributions in both the induction and suppression of AHR. Thus, TLR signaling is likely required for both the development of asthma and the suppression of asthma by S. pneumoniae, and potentially other immunoregulatory therapies.